Antitrypanosomal activities of proteasome inhibitors - Nkemngu, Njinkeng; Rosenkranz, Vera; Wink, Michael; Steverding, Dietmar (Antimicrobial agents and chemotherapy, 2002)
Seven peptidyl proteasome inhibitors were tested for in vitro activity against Trypanosoma brucei bloodstream forms. Two compounds showed activity in the low nanomolar range. In general, trypanosomes were more susceptible to the compounds than were human HL-60 cells. The data support the potential of proteasome inhibitors for rational antitrypanosomal drug development.